2020
DOI: 10.3390/nu12020393
|View full text |Cite
|
Sign up to set email alerts
|

Free and Added Sugar Consumption and Adherence to Guidelines: The UK National Diet and Nutrition Survey (2014/15–2015/16)

Abstract: Monitoring dietary intake of sugars in the population's diet has great importance in evaluating the efficiency of national sugar reduction programmes. The study objective was to provide a comprehensive assessment of dietary sources of added and free sugars to assess adherence to public health recommendations in the UK population and to consider the impact of different sugar definitions on monitoring. The terms "added sugar" and "free sugar" are different sugar definitions which include different sugar componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 24 publications
4
35
4
Order By: Relevance
“…Children and adolescents in Portugal [54], Spain [55], Slovenia [56], Colombia, and Ecuador [43] had a mean intake of 9.5-11.6%E and 9.8-10.1%E, respectively. The intake in this study was lower than that in previous studies; in particular in the Netherlands [57], the UK [58], the US [42], Argentina, Brazil, Chile, Costa Rica, Peru, and Venezuela [43] (12.9-18.4%E and 17.6-20.7%E, respectively). Most literatures that reported significant associations of cardiometabolic risks came from the US [45,46,49], where the prevalence of metabolic syndrome based on the IDF definition, i.e., 5.2-9.5% at age 14 years [59,60] was higher than that in the current study.…”
Section: Discussioncontrasting
confidence: 83%
“…Children and adolescents in Portugal [54], Spain [55], Slovenia [56], Colombia, and Ecuador [43] had a mean intake of 9.5-11.6%E and 9.8-10.1%E, respectively. The intake in this study was lower than that in previous studies; in particular in the Netherlands [57], the UK [58], the US [42], Argentina, Brazil, Chile, Costa Rica, Peru, and Venezuela [43] (12.9-18.4%E and 17.6-20.7%E, respectively). Most literatures that reported significant associations of cardiometabolic risks came from the US [45,46,49], where the prevalence of metabolic syndrome based on the IDF definition, i.e., 5.2-9.5% at age 14 years [59,60] was higher than that in the current study.…”
Section: Discussioncontrasting
confidence: 83%
“…Adherence of the Slovenian population to the WHO guidelines to consume less than 10% TEI in free sugars was higher compared to that in other countries; more than half of the Slovenian adolescents and as many as 84% of adults and 81% of the elderly met the recommendation. In a similar study conducted in Switzerland, 36% of adolescents, 45% of adults, and 53% of the elderly reported free sugars consumption below 10% TEI [42], whereas in the U.K., the same criteria were met by 27% of adolescents and 54% of the adult participants [34]. Only Portugal has reported comparably high or even higher percentages of adherence to the guidelines than reported in the present study (51.3% among adolescents, 68.9-85.1% among adults, and 92.1% among the elderly) [45].…”
Section: Discussionmentioning
confidence: 86%
“…The results indicated that habitual consumption of total and free sugars is the highest among 10-17-year-olds, which is in line with other studies, although the reported intakes are somewhat lower compared to the other European countries. In the U.K. National Nutrition Survey (2014-2016), teenagers were reported to consume on average 13% TEI from free sugars [34]. The results from the Dutch National Food Consumption Survey occurring 2007-2010 were even more alarming, with the reported median daily intake of free sugars in adolescents being as high as 17.6-19.8% TEI [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to children and adolescents, a scientific statement published by the American Heart Association (AHA) in 2017 recommends <25 g of added sugars per day, although added sugar should not be included in the diet for children <2 years of age (16). According to a recent study, in UK added or free sugar intake has been estimated between 7% and 13% of total energy intake, respectively, and it is higher in children than in adults (17). The prevalence of obesity and its comorbidities (such as type 2 diabetes, cardiovascular diseases and cancer) has dramatically increased (18) and several governments started to promote policies aimed to encourage a healthy diet and lifestyle (19).…”
Section: Introductionmentioning
confidence: 99%